H alomonas sulfidaeris ‐dominated microbial community inhabits a 1.8 km‐deep subsurface C ambrian S andstone reservoir - Yiran Dong; Charu Gupta Kumar; Nicholas Chia; Pan‐Jun Kim; Philip A. Miller; Nathan D. Price; Isaac K. O. Cann; Theodore M. Flynn; Robert A. Sanford; Ivan G. Krapac; Randall A. Locke; Pei‐Ying Hong; et al. (Environmental Microbiology, 2014)
Summary A low‐diversity microbial community, dominated by the γ ‐proteobacterium H alomonas sulfidaeris , was detected in samples of warm saline formation porewater collected from the C ambrian Mt. S imon S andstone in the I llinois B asin of the N orth A merican M idcontinent (1.8 km/5872 ft burial depth, 50° C , pH 8, 181 bars pressure). These highly porous and permeable quartz arenite sandstones are directly analogous to reservoirs around the world targeted for large‐scale hydrocarbon extraction, as well as subsurface gas and carbon storage. A new downhole low‐contamination subsurface sampling probe was used to collect in situ formation water samples for microbial environmental metagenomic analyses. Multiple lines of evidence suggest that this H . sulfidaeris ‐dominated subsurface microbial community is indigenous and not derived from drilling mud microbial contamination. Data to support this includes V 1‐ V 3 pyrosequencing of formation water and drilling mud, as well as comparison with previously published microbial analyses of drilling muds in other sites. Metabolic pathway reconstruction, constrained by the geology, geochemistry and present‐day environmental conditions of the Mt . S imon S andstone, implies that H . sulfidaeris ‐dominated subsurface microbial community may utilize iron and nitrogen metabolisms and extensively recycle indigenous nutrients and substrates. The presence of aromatic compound metabolic pathways suggests this microbial community can readily adapt to and survive subsurface hydrocarbon migration.

Impact of urban development on the chemical composition of ground water in a fen-wetland complex - Samuel V. Panno; Victoria A. Nuzzo; Keros Cartwright; Bruce R. Hensel; Ivan G. Krapac (Wetlands, 1999)